2020
DOI: 10.1002/wat2.1477
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies for individual and household‐level water insecurity: A systematic review

Abstract: Household water insecurity is a complex socioecological challenge with a range of consequences for health and wellbeing. Understanding individual and household‐level coping strategies, i.e., responses or adaptations to manage water insecurity, can shape future research and development practice. We therefore (a) systematically describe the characteristics and contexts of 173 studies documenting coping strategies and (b) classify the types of strategies within four domains of water insecurity: access, use, quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 98 publications
6
28
0
Order By: Relevance
“…In many contexts household water managers often experience psychosocial stress as a result of the negotiations, such as borrowing, purchasing, or rationing water, in which they must engage to ensure sufficient water (Wutich & Ragsdale, 2008; Brewis, 2019a; Stevenson et al, 2012). Marginalized households with low socioeconomic status often rely on less costly but more time-consuming coping mechanisms for water insecurity, which may contribute to even greater stress among those households (Achore et al, 2020; Venkataramanan et al, 2020). We found that lower perceived standing was associated with higher odds of borrowing water.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In many contexts household water managers often experience psychosocial stress as a result of the negotiations, such as borrowing, purchasing, or rationing water, in which they must engage to ensure sufficient water (Wutich & Ragsdale, 2008; Brewis, 2019a; Stevenson et al, 2012). Marginalized households with low socioeconomic status often rely on less costly but more time-consuming coping mechanisms for water insecurity, which may contribute to even greater stress among those households (Achore et al, 2020; Venkataramanan et al, 2020). We found that lower perceived standing was associated with higher odds of borrowing water.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also show that households experience and cope with water insecurity differently based on their wealth and socioeconomic status (Achore et al, 2020; Venkataramanan et al, 2020). To account for these differences three measures of socioeconomic status were used: livestock wealth, household income, and perceived standing in the community.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Households may cope with water scarcity and contamination by consuming less food or changing diets, sometimes replacing preferred foods with less nutrient-dense or more highly processed substitutes that require little or no water to prepare ( 127 ). In Kenya, 2 studies found that households had sufficient food but were unable to use it because they lacked water (e.g., for preparing porridge) ( 81 , 128 ).…”
Section: Current Status Of Knowledgementioning
confidence: 99%